Robotic natural orifice specimen extraction surgery versus conventional robotic resection for patients with colorectal neoplasms - Li, Linye; Liu, Kuijie; Li, Tiegang; Zhou, Jiangjiao; Xu, Shu; Yu, Nanhui; Guo, Zhushu; Yao, Hongliang (Frontiers in Oncology, 2023)
Background: Laparoscopic natural orifice specimen extraction surgery (NOSES) has been widely used in colorectal neoplasms. However, only a few studies have focused on robotic NOSES. This study compared the short-term clinical outcomes and long-term survival outcomes between robotic NOSES and conventional robotic resection (CRR) groups. Methods:From March 2016 to October 2018, a consecutive of 143 patients who underwent robotic sigmoid and rectal resection at the Department of Gastrointestinal Surgery, The Second Xiangya Hospital, Central South University, were considered for inclusion in this study. Propensity-score matching (PSM) was conducted to account for differences in the baseline characteristics. After PSM, 39 patients were included in the robotic NOSES group, and 39 patients in the CRR group. The baseline characteristics between the two groups were all balanced and comparable. Results: Patients in the NOSES group experienced less intraoperative blood loss (p=0.001), lower requirements for additional analgesia (p=0.020), shorter time to first flatus (p=0.010), and a shorter time to first liquid diet (p=0.003) than the CRR group. The 3-year overall survival rates (NOSES: 92.3% vs. CRR: 89.7% p=1.000) and 3-year disease-free survival rates (NOSES: 82.1% vs. CRR: 84.6% p=0.761) between the two groups were comparable. Conclusion: Robotic natural orifice specimen extraction surgery is a safe and feasible surgery for patients with colorectal neoplasms. Robotic NOSES is associated with better short-term clinical outcomes and similar long-term survival outcomes to conventional robotic resection.